Modeling the World Economic Outlook At the IMF : A Historical Review - Boughton, James (IMF Working Papers; Working Paper ;, 1997)
The World Economic Outlook (WEO) exercise at the IMF evolved during the 1980s, partly in response to demands by policymakers in national finance ministries for objective and internationally comparable projections and policy scenarios. The exercise had begun as a staff initiative, encouraged by the Managing Director (Johannes Witteveen). Gradually, the Executive Board, the Interim Committee, the Group of Seven, and others came to view the discussion of the WEO documents as an important element in their efforts to keep abreast of world economic developments and prospects. Direct and indirect feedback from those discussions informed the staff as to how the exercise should be improved. Driven by this policy relevance, the WEO evolved from a decentralized project that was only haphazardly model-based into a more rigorous and coordinated exercise.